Entering the field: initiating liturgical research in an African Independent Church (AIC) - C. Wepener; M. Barnard (Acta Theologica)
African Independent Churches (AICs) have been studied by scholars from various disciplines, especially Missiology and Anthropology, making use of various methods including participatory observation. In Ritual and Liturgical Studies, AICs and their abundance of rituals is still a rather under-explored field of research with several reasons making it a difficult area to access. In this article, one aspect of participatory observation in researching ritual action in AICs will be explored, namely the initial phase of entering the field. Real examples from a current South African National Research Foundation (NRF)-funded research project as conducted by a team of scholars including some from the field of Ritual and Liturgical Studies will first be described and thereafter discussed. Diachronically, the initial phase stretching from a pre-proposal workshop until the first attendance of a worship service in a local congregation is sketched and commented upon.